Artemisia - Ferlut, Nathalie, 1968- (Beehive Books, 2021)
"This full-color graphic novel recounts the remarkable story of Artemisia, whose life story is told through the lens of Artemisia's daughter as she questions her mother about their family history. The ensuing tale spans most of Gentileschi's life, beginning with her childhood in Rome in her father's painting studio, to the sexual abuse she experienced at the hands of a tutor and the arduous trial that followed, as well as the highlights of her prolific career in which she received commissions from clients as powerful as the Medici and the English royal family and became the first woman admitted to the prestigious Academy of Arts in Florence."--Amazon.com